Preschool Teachers' Implicit Beliefs on Children's Nature and the Opportunities for Children's Development - Blagica M. Zlatković; Мilica N. Ristić (University of Belgrade, Teacher Education Faculty, 2020)
The paper looks at the results of the research conducted with the aim of determining preschool teachers' implicit beliefs on children's nature and the opportunities for fostering children's development at preschool level in order to shed more light on the "internal model"that preschool teachers are guided by in their everyday work. The research was conducted on a convenience sample of preschool teachers (N = 38). The gender structure of the sample was homogenous, given that it consisted only of female preschool teachers. The authors designed a Questionnaire on Preschool Teachers' Beliefs which was used as the research instrument. The obtained results were analysed using both quantitative and qualitative procedures. The quantitative analysis involved determining the frequency of some categories of responses. The qualitative analysis was conducted in the coding of the responses to open-ended questions according to their meaning into broader categories, as well as in the more detailed analysis of two respondents' answers to all the questions in the Questionnaire. The questionnaires for the detailed analysis were selected according to the predominating adherence to either incremental or entity theoretical orientation, i.e., the responses given by the two respondents were closest to the poles of the entity-incremental orientation. The research results indicate that the preschool teachers who participated in the survey hold different implicit beliefs on children's nature and the opportunities for influencing their development and that these beliefs, more or less, match their incremental or entity beliefs. More specifically, the teachers' implicit beliefs are distributed on a continuum of entity-incremental orientation, with a simultaneous representation of conflicting beliefs in some respondents. The absence of complete coherence of implicit beliefs was registered in the qualitative analysis of the answers within one questionnaire.